Hemispheres and Stratospheres The Idea and Experience of Distance in the International Enlightenment. - Cope, Kevin L.; Lund, Roger D.; Stargard, William; Czennia, Bärbel; Singh, Brijraj; Chakravarty, Chandrava; Mann, Rachel; Thompson, Phyllis (Transits (Bucknell University), 2020)
"Nowhere is distance so near-at-hand as in Enlightenment culture. Whether in the telescopic surveys of early astronomers, the panoramas of painters, the diaries of travelers, the prospects of landscape architects, or the tales of novelists, distance is never far in the background of the works and deeds of long-eighteenth-century artists, authors, and adventurers. Hemispheres and Stratospheres draws that background into the foreground. Recognizing distance as a central concern of the Enlightenment, this volume offers eight essays on distance in art and literature; on cultural transmission and exchange over distance; and on distance as a topic in science, a theme in literature, and a central issue in modern research methods. Through studies of landscape gardens, architecture, imaginary voyages, transcontinental philosophical exchange, and cosmological poetry, Hemispheres and Stratospheres unfurls the early history of a distance culture that influences our own era of global information exchange, long-haul flights, colossal skyscrapers, and space tourism"--